Characterization of Sand Dunes to Detect the Sand Source and their Stabilization, Abardej, Iran - Roudgarmi, Pezhman; Farahani, Ebrahim (International Journal of Geography and Geology, 2015)
A dune field was investigated to detect dunes morphology, physiochemical and mineralogical specifications in Abardej region in the southeast of Tehran, Iran. The border of dunes was determined using aerial photographs and field observations, and then the various shapes of dunes were found. The results have shown that dune shape is mostly transverse, indicating the existence of a dominant wind in one direction. Also, there are some Nebka dunes infrequently. Based on the chemical analysis of dunes, there isn’t any limitation for cultivation of desert plants, and the biologic stabilization of dunes is possible and suitable. The morphoscopic study has shown that the sand grains almost have steep angles; therefore, the dunes may have local sources. The sand grains were almost shiny and semi-shiny in microscope’s light, indicating that the source of dunes is generally the river-beds. Quartz, Feldspar and Calcite were the main minerals of sand grains. The mean of sampled sand grains diameter was about 200 microns and 27 percent of them had a diameter of 250 microns or more; these reveal the existence of a local source for the dunes. Based on the obtained results, it would be concluded that the source of sand dunes is floodplains in east and south- east of the dunes.